OPTIMALISASI PENGETAHUAN PETUGAS AHLI TEKNOLOGI LABORATORIUM MEDIS DALAM PENANGANAN SPESIMEN FESES DENGAN PENAMBAHAN ETANOL - Idayani, Sri; Trisnadewi, Ni Wayan; Pramesti, Theresia Anita; Lestari, Ni Kadek Yuni; Putra, I Gusti Putu Agus Ferry Sutrisna (Universitas Islam Malang, 2025)
In improving the quality of laboratory examinations, Medical Laboratory Technologists (ATLM) need information about specimen storage, including specimen handling. One way to diagnose Soil Transmitted Helminths (STH) Infections is through fecal examination. With the limited number of fecal samples, this activity is expected to improve the knowledge and skills of ATLM at the Denpasar Utara III Health Center, so it is important to have socialization and demonstrations regarding the handling of fecal specimens. The purpose of this activity is to improve the ability of ATLM in handling fecal specimens with the addition of ethanol to the quality of worm eggs. The method of implementing this community service is carried out by providing socialization in the form of education through lectures using powerpoint and LCD media and continued with demonstrations and evaluations in the form of the results of filling out the google form before and after education and demonstrations. ATLM officers were very enthusiastic in participating in the activity and actively asked questions both about handling fecal specimens and making ethanol solutions. In addition, the indicator of the success of this activity is an increase in the ability to carry out laboratory examinations, especially in parasite examinations, with an emphasis on proper specimen handling. By adding a diluted ethanol solution as needed to maintain the quality of the specimen in preventing damage to the specimen before further examination, so that the quality of the worm eggs obtained through microscopic examination will be better.